2018
DOI: 10.1108/pr-03-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Biting the hand that heals: mistreatment by patients and the well-being of healthcare workers

Abstract: Purpose The purpose of this paper is to explore the relationship between stress due to mistreatment by patients and caregivers’ own well-being indicators (anxiety, depression, and behavioral stress indicators). Based on predictions consistent with the job demands-resources model, it is anticipated that satisfaction with job resources would moderate the relationship between mistreatment by patients and well-being indicators. Design/methodology/approach Hypotheses were tested with a sample of 182 employees in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 60 publications
(84 reference statements)
2
17
0
Order By: Relevance
“…Mistreatment by patients concerns rude, threatening, or aggressive behaviors directed at nurses [16], such as verbal insults or physical pushing. As a kind of job pressure, mistreatment influences employees' recognition, emotional state, and behaviors [3]. Numerous studies have documented the negative effects of low-quality interpersonal treatment on service employees.…”
Section: Mediating Role Of Work Meaningfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Mistreatment by patients concerns rude, threatening, or aggressive behaviors directed at nurses [16], such as verbal insults or physical pushing. As a kind of job pressure, mistreatment influences employees' recognition, emotional state, and behaviors [3]. Numerous studies have documented the negative effects of low-quality interpersonal treatment on service employees.…”
Section: Mediating Role Of Work Meaningfulnessmentioning
confidence: 99%
“…According to the Chinese Medical Occupation Status White Paper issued by the Chinese Medical Doctor Association in 2018, 41.2% nurses have experienced mistreatment by a patient within the previous year [1]. This phenomenon (including verbal abuse, incivility, aggression) of patients mistreating nurses by making undeserved prejudicial statements or engaging in hurtful personal attacks can be described as mistreatment by patients [2,3]. As Grandey et al found, mistreatment by service users is a common but problematic occurrence in the workplace [4].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that different patients and their relatives’ behaviour contributes to the SS of HCWs. In 2017, 41.2% of Chinese nurses experienced mistreatment by patients ( 15 ). Twenty-two percent of nurses from 10 European Countries reported frequent relatives ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…
It is an unfortunate reality that employees at greatest risk of violence are those working in roles that serve the health and wellbeing of the community (Karaeminogullari, Erdogan, & Bauer, 2018). Paramedics are especially susceptible to injury as they work in uncontrolled and potentially volatile conditions, compounded by exposure to traumatic events (Bigham et al, 2014).
…”
mentioning
confidence: 99%
“…Despite a significant number of assault-related injuries, surprisingly little is known about the situational risk factors associated with violence against paramedics (Wongtongkam, 2017).Work-related violence is defined as any incident whereby a person is abused, threatened, or assaulted (physically, verbally or sexually -including threats) in a scenario pertaining directly to their chosen occupation (Loudoun & Johnstone, 2019). Violence at work is a problematic and undesirable behaviour affecting employees, colleagues, leaders, HR Managers, and communities and stakeholders more broadly (Karaeminogullari et al, 2018). The impact of violence against paramedics cannot be understated.…”
mentioning
confidence: 99%